2010
DOI: 10.1007/s11199-010-9854-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Children’s Occupational Aspirations as a Function of Parental Traditionality

Abstract: The current study was designed to test the application of the social-cognitive theory of gender development in predicting the traditionality of children's occupational aspirations (Bussey and Bandura 1999). Of primary interest was the influence of children's efficacy for nontraditional tasks on their occupational aspirations. Participants were 150 children and their mothers from the southern United States. Mothers reported their gendered attitudes, their perception of their children's skills, and their family'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Fulcher (2010) found that when middle-class mothers held more traditional ideas about children's gender roles, their children (ages 7 to 12) tended to report more gender-stereotyped career aspirations. Specifically, when mothers expected their children to be interested in traditionally gendered careers, children expressed more interest in careers that promote gender stereotypes.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Fulcher (2010) found that when middle-class mothers held more traditional ideas about children's gender roles, their children (ages 7 to 12) tended to report more gender-stereotyped career aspirations. Specifically, when mothers expected their children to be interested in traditionally gendered careers, children expressed more interest in careers that promote gender stereotypes.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have tended to overlook the ways in which both mothers and fathers contribute to their children’s gender socialization in unique ways, often relying on mothers' reports of fathers' behavior (Fulcher, 2010) or overlooking fathers entirely (e.g., Cunningham 2001a & 2001b). The current study considers the potential for both mothers’ and fathers' ideologies and performance of gendered behavior to predict their children's gender-role attitudes in the context of two-parent, heterosexual families.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents often provide children with gender-typed toys, activities, and environments (Wood et al 2002) and influence children's development of gender stereotypes by engaging in a traditional or nontraditional division of labor. Children whose parents' engage in traditional gender roles endorse more gender stereotypes than children whose parents' engage in nontraditional gender roles (Fulcher 2011). Starting in preschool, children begin to select into gender-segregated play groups, and play with other gender peers is limited (Maccoby 1998).…”
mentioning
confidence: 99%